Pengaruh Dimensi Corporate Governace Terhadap Nilai Perusahaan pada Perusahan LQ45 di Bursa Efek Indonesia - Eliadi, Suhailla; Syailendra Eka Putra; Vivina Eprillison (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was carried out to analyze the influence of corporate governance dimensions on company value in companies included in the LQ45 index on the Indonesia Stock Exchange during the 2019–2024 period. Corporate governance in this research is measured through several indicators, namely the proportion of independent commissioners, audit committee size, number of commissioners' meetings, managerial ownership and public ownership. The research uses a quantitative approach with a population of 45 companies. Sample selection was carried out using a purposive sampling technique based on certain criteria relevant to the research objectives. Data analysis uses panel data regression with the help of Stata 15 software so that the results obtained are more accurate and reliable. The research results show that the proportion of independent board of commissioners, size of the audit committee, number of board of commissioners meetings, and managerial ownership do not have a significant effect on company value. On the other hand, public ownership is proven to have a significant influence on company value. The simultaneous test also revealed that all the corporate governance variables analyzed did not have a significant influence on company value. This finding emphasizes that external factors outside the formal governance structure play a more important role in determining company value. The implication is that companies need to pay attention to other aspects outside corporate governance, while for investors, independent analysis of financial performance and business strategy is very important before making investment decisions.